Kesiapan Kerja Penyandang Disabilitas: Dampak Dukungan Sosial dan Motivasi Melalui Employability Skill - Nur Cahyadi (Jurnal Manajerial, 2026)
Background – People with disabilities still face various barriers in entering the workforce, especially those related to work readiness. Low work readiness is not only influenced by individual limitations, but also by environmental factors such as social support and psychological factors such as motivation. However, empirical studies that integrate the role of social support and motivation on work readiness through employability skills are still limited, especially from the perspective of inclusive human resource management. Aim – This study aims to analyze the influence of social support and motivation on the work readiness of persons with disabilities through employability skills as an intervening variable. Design / methodology / approach – This study uses a quantitative approach with a survey method. Data were collected through questionnaires administered to 64 people with physical disabilities in Gresik Regency, who were selected using purposive sampling. Data analysis was performed using Partial Least Squares (PLS)-based Structural Equation. Findings – The results show that social support has a positive and significant effect on employability skills. Conversely, motivation does not have a significant effect on employability skills. Employability skills also do not have a significant effect on work readiness. In addition, employability skills are not proven to mediate the influence of social support or motivation on the work readiness of persons with disabilities. Conclusion - This study shows that social support plays an important role in improving the employability skills of people with disabilities. Support from family, community, and the surrounding environment has been proven to encourage the development of work skills. Conversely, motivation does not have a significant effect on employability skills, meaning that internal motivation alone is not enough to improve work skills without adequate environmental support. In addition, employability skills also do not have a significant effect on work readiness, indicating that possessing work skills does not directly reflect readiness to enter the workforce. This study also found that employability skills do not mediate the influence of social support or motivation on work readiness. Thus, the work readiness of persons with disabilities is influenced by factors other than individual skills and motivation, such as labor market conditions and an inclusive work environment. Research implication – The findings of this study imply that improving the employability of persons with disabilities requires more than just strengthening individual motivation and skills; it also requires strong social support and an inclusive employment environment and policy. This study enriches the field of human resource management by emphasizing the importance of a holistic approach to managing the workforce of persons with disabilities. Limitations – This study is limited to people with physical disabilities in one research area with a relatively small sample size, so the results cannot be generalized broadly.